Nanocrystalline materials dispersed in vinyl-containing polymers and methods thereof

By using nanocrystalline cellulose and polydimethylsiloxane in vinyl PVC film, the instability and printing performance of vinyl PVC film under weather and UV radiation is solved, and a higher level of Thermal stability and printing suitability extend the service life of the film.

CN114466870BActive Publication Date: 2025-01-07AVERY DENNISON CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080068438.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-20
Filing Date
2020-07-30
Publication Date
2025-01-07
Estimated Expiration
2040-07-30

AI Technical Summary

Technical Problem

Existing vinyl PVC films are prone to become unstable when exposed to weather and UV radiation, resulting in degradation, cracking, stratification and other physical changes. At the same time, printing performance is inconsistent, and the added stabilizers are prone to migrating, affecting the long-term use of the film.

Method used

Using a poly(vinyl chloride) resin composition containing nanocrystalline cellulose (NCC), a film that improves printing suitability and weather resistance is formed by combining with organic liquids and polydimethylsiloxanes to reduce the stabilization agent. Migrate and optimize solubility to improve membrane performance.

Benefits of technology

It improves the thermal stability and printing performance of vinyl film, extends the service life of the film, reduces the migration of stabilizers, enhances the weather resistance and printing suitability of the film, and ensures better physical performance and long-term stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114466870B_ABST
    Figure CN114466870B_ABST
Patent Text Reader

Abstract

Described herein are vinyl resin compositions comprising nanocrystalline materials, films formed therefrom, laminates formed from such films, and methods of making and using the same.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Patent Application No. 62 / 883,179, filed on August 6, 2019, and U.S. Provisional Patent Application No. 62 / 937,826, filed on November 20, 2019, the entire disclosures of which are incorporated herein by reference in their entireties. Technical Field

[0003] The present subject matter relates to compositions comprising one or more polymer resins having one or more nanocrystalline materials dispersed or suspended therein, films made from such compositions, laminates made from such films, and methods of making and using the same. The resulting compositions and films exhibit a variety of beneficial or improved properties, including improved printability and weather stability. Background Art

[0004] Poly(vinyl chloride) or polyvinyl chloride (PVC) is a widely produced synthetic plastic polymer. The two basic forms of PVC are flexible and rigid. Flexible PVC, hereinafter referred to as vinyl film, is very useful in packaging and other decorative items. The decorative items may include, but are not limited to, pressure sensitive labels, fleet graphics, automotive wraps, and retroreflective eye-catching articles.

[0005] In order to make PVC flexible, plasticizers must be added. In many applications, vinyl can become unstable due to exposure to weather and UV radiation. Acid scavengers, heat stabilizers, and / or UV stabilizers can be added to PVC to alleviate these problems. All of these additives are not miscible with PVC and will gradually migrate from the vinyl film. Once these additives are exhausted, the vinyl film begins to degrade. Weathering of vinyl often results in cracking, delamination, browning, shrinkage, or other undesirable physical changes in the product.

[0006] Many vinyl film products receive indicia, text and / or graphic designs printed along the outer surface of the product. Printing on vinyl films is often accompanied by inconsistent performance and / or appearance between printed areas or regions on the product. In addition, differences in printed image quality, intensity and / or resolution may also occur between printed areas on the product. Printability characteristics can be improved by adding additives to the vinyl film formulation. However, the addition of additives increases the number of manufacturing steps and / or manufacturing costs. Therefore, there is a need for flexible vinyl films with improved printability characteristics.

[0007] Nanocrystalline cellulose can be added to PVC formulations for a variety of reasons, including (1) self-assembly to form structured liquid crystals; (2) strength due to high levels of crystallinity; (3) thixotropy (shear thinning); (4) reactivity (the surface has hydroxyl and acid groups that are reactive and can be functionalized to change properties); (5) photonics (forming solids with structural colors that produce pearlescent and iridescent effects); and (6) electromagnetic properties (functional groups impart a negative charge to the surface, imparting electromagnetic properties to the crystal).

[0008] Flexible PVC film can be manufactured by casting or calendering. When manufacturing the cast PVC film involving an organosol containing an organic liquid, adding nanocrystalline cellulose in the form of a water-based gel solution can cause compatibility problems (because nanocrystalline cellulose has very high surface energy and polar side branches relative to the organic liquid in the organosol). Therefore, nanocrystalline cellulose cannot be properly mixed into the organosol of the cast PVC film, and nanocrystalline cellulose forms agglomerates and aggregates in the PVC film. This has led to problems including the need to use higher levels of nanocrystalline cellulose to achieve the same performance. Similarly, when manufacturing the calendered PVC involving melting and mixing PVC powder, adding nanocrystalline cellulose in powder form can also cause problems.

[0009] Therefore, there is a need for methods for forming composites comprising PVC and nanocrystalline cellulose that alleviate these problems. The embodiments described herein address these and other important needs. SUMMARY OF THE INVENTION

[0011] Described herein are vinyl resin compositions, films formed therefrom, laminates formed from such films, and methods of making and using the same. In some embodiments, the composition or film comprises one or more nanomaterials. In some embodiments, the one or more nanomaterials comprise or are nanocrystalline cellulose (NCC) or cellulose nanocrystals (CNC). Nanocrystalline cellulose (NCC) has many advantageous properties, including: (1) self-assembly to form structured liquid crystals; (2) strength due to high levels of crystallinity; (3) thixotropy (shear thinning); (4) reactivity (surfaces have reactive hydroxyl groups and acid groups that can be functionalized to change properties); (5) photonics (forming solids with structural colors that produce pearlescent and iridescent effects); and (6) electromagnetic properties (functional groups generate negative charges on the surface, thereby imparting electromagnetic properties to the crystals).

[0012] NCC can improve the stability of additives such as plasticizers, acid scavengers, UV stabilizers, heat stabilizers, print enhancement additives and solvents / diluents. Adding NCC can improve the digital printing performance of vinyl resins (e.g., PVC) without using additives that can migrate from the film. Vinyl resin solutions containing NCC have lower contact angles than resin solutions without NCC, indicating better "wetting" of the ink or adhesive.

[0013] One embodiment is directed to a composition comprising: at least one poly(vinyl chloride) resin; at least one nanocrystalline cellulose; at least one organic liquid suitable for suspending or dispersing the poly(vinyl chloride) resin; at least one polydimethylsiloxane; and optionally, at least one surfactant.

[0014] Another embodiment is directed to a method comprising: providing a composition into a reactor, wherein the composition comprises: vinyl chloride monomer, nanocrystalline cellulose, and water; polymerizing the composition to form a composite, wherein the composite comprises: poly(vinyl chloride) and nanocrystalline cellulose; wherein the composite is in the form of an aqueous dispersion. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The accompanying drawings are included to provide a further understanding of the present invention and are incorporated in and constitute a part of this specification. The accompanying drawings illustrate embodiments of the present invention and together with the description serve to explain the principles of the present invention. In the drawings:

[0017] Figure 1 is a schematic diagram of one embodiment of a method of forming poly(vinyl chloride).

[0018] Figure 2 is a graph evaluating thermal stability by measuring critical conductance time (seconds) as a function of nanocrystalline cellulose (NCC) concentration.

[0019] Figure 3 Shows the dot shape of solvent-based ink with the addition of NCC.

[0020] Figure 4 is a graph showing the thermal stability of PVC films with different NCC loadings.

[0021] Implementation Detail

[0022] The present subject matter provides a flexible vinyl film with improved properties including improved printability and weatherability. The vinyl film is formed from a composition comprising one or more PVC resins, NCC and at least one plasticizer. The composition may optionally include at least one UV stabilizer, at least one heat stabilizer and / or at least one printing additive. In many embodiments, the vinyl composition can be further improved by changing the relationship between the components in the formulation. In certain applications, it may be beneficial to reduce the solubility between the components; this is especially true for components that need to be located on the surface. However, in other applications, it may be desirable to optimize solubility.

[0023] The present theme also provides laminates utilizing vinyl films, particularly those described herein. Typically, the laminate comprises a vinyl layer, a first adhesive layer near the vinyl layer. The laminate may additionally include a liner disposed on the first adhesive layer. However, more complex retroreflective laminates also include a spacing layer, an optical component area, and a metallized layer, wherein the optical component area may be in the form of glass beads, for example, dispersed between the first adhesive layer and the spacing layer. The vinyl layer or film is formed by an organosol as described herein. These laminates may additionally include a second adhesive layer that typically covers the metallized layer, and a liner disposed on the second adhesive layer. All of these laminates, variants thereof, and additional products are described herein.

[0024] The present subject matter further provides methods of producing the laminated articles and / or vinyl films. Vinyl films can be produced using a variety of techniques, particularly using an organosol casting process. These and other aspects of the present subject matter are described herein.

[0025] I. Definitions

[0026] As used above and throughout this disclosure, the following terms, unless otherwise indicated, shall be understood to have the following meanings.

[0027] As used herein, the terms "comprises / comprising", "includes / including", "has / having" or any other variation thereof are intended to be open-ended and encompass non-exclusive connotations. For example, a process, method, article, or device that includes a list of elements is not necessarily limited to those elements, but may include other elements that are not explicitly listed or inherent to such process, method, article, or device. In addition, "one" or "a kind" are used to describe the elements and components described herein. This is done merely for convenience and to give a general sense of the scope of the invention. The description should be understood to include "one" or "at least one", and the singular also includes the plural, unless the context clearly indicates otherwise. As used herein, the term "about" when referring to a measurable value such as an amount, is intended to include changes of ±10%, preferably ±8%, more preferably ±5%, even more preferably ±1%, and even more preferably ±0.1% from a given value, because such changes are suitable for carrying out the disclosed method.

[0028] As used herein, "pressure sensitive adhesive" or "PSA" refers to a material that can be identified by the Dahlquist standard, which defines a pressure sensitive adhesive as having a pressure greater than 1×10 -6 cm 2 / dyne (dyne) 1 second creep compliance, as described in Handbook of PSA Technology, Donatas Satas (ed.), 2nd edition, page 172, Van Nostrand Reinhold, New York, NY, 1989. Since the modulus is the inverse of the creep compliance to a first approximation, a pressure sensitive adhesive can also be defined as having a creep compliance of less than 1×10 6 Dyne / cm 2Another well-known method of identifying a pressure sensitive adhesive is one that is aggressively and permanently tacky at room temperature, adheres securely to a variety of different surfaces upon contact without more than finger or hand pressure, and can be removed from smooth surfaces without leaving residue, as described in the terminology used in the Glossary of Terms Used in the Pressure Sensitive Tape Industry provided by the Pressure Sensitive Tape Council in 1996. Another suitable definition of a suitable pressure sensitive adhesive is that it preferably has a room temperature storage modulus within the region defined by the following points plotted on a graph of modulus versus frequency at 25°C: a modulus range of about 2×10 5 Up to 4×10 5 Dyne / cm 2 , at a frequency of about 100 rad / s (17 Hz), the modulus ranges from about 2 × 10 6 Up to 8×10 6 Dyne / cm 2 See, for example, Handbook of PSA Technology, Donatas Satas (Ed.), 2nd edition, page 173, Van Nostrand Reinhold, NY, 1989. Any of these methods of identifying pressure sensitive adhesives can be used to identify pressure sensitive adhesives suitable for use in the film structures described herein.

[0029] Unless otherwise indicated, all percentages stated herein are by weight percentages based on the weight of the composition.

[0030] As used herein, "organosol" generally refers to a resin (e.g., a vinyl-containing polymer resin) suspended or dispersed in an organic fluid, particularly an organic liquid (e.g., diisobutyl ketone), for example, at a level of 5% to 25% by weight based on the total weight of the organosol formulation. The films described herein can be cast from the organosol.

[0031] As used herein, "PVC" refers to a vinyl-containing resin, and more specifically, refers to polyvinyl chloride formed by polymerization of vinyl chloride monomer. Alternatively, PVC or polyvinyl chloride is referred to herein as poly(vinyl chloride).

[0032] II. Compositions and Films

[0033] A. Vinyl-containing resin

[0034] The compositions and films made from the compositions described herein include one or more vinyl-containing resins. Exemplary resins include, but are not limited to, polyvinyl chloride (PVC) or poly(vinyl chloride). In some embodiments, one or more resins include or are PVC. A variety of PVC resins can be used. Polyvinyl chloride is a resin with the chemical formula (C2H3Cl) n In some embodiments, the molecular weight of the PVC resin ranges from about 25,000 to about 250,000. However, it should be understood that the present subject matter includes the use of PVC resins having molecular weights outside of this range.

[0035] In some embodiments, the PVC is a low molecular weight PVC, a medium molecular weight PVC, a high molecular weight PVC, or a combination thereof. These terms "low molecular weight", "medium molecular weight" and "high molecular weight" refer to PVC resins having the following K values ​​and / or molecular weights.

[0036] Table 1: PVC resins used in vinyl compositions and vinyl layers

[0037] PVC resin Typical K-value Specific K-value Typical molecular weight Specific molecular weight Low molecular weight 48-72 68 34,700-101,900 87,600 Medium molecular weight 72-80 76 102,000-134,800 117,700 High molecular weight 80-92 83 134,900-195,500 148,700

[0038] As known in the art, the K-value is an indication of the average molecular weight of a polymer sample or resin. The K-value is a molecular weight metric based on viscosity measurements and is described in more detail in "Encyclopedia of Polymer Science and Technology" Vol. 14, John Wiley & Sons (1971); and "Molecular Weight and Solution Viscosity Characterization of PVC", Skillicorn, DE, Perkins, GGA, Slark, A., and Dawkins, JV, Journal of Vinyl Technology, June 1993, Vol. 15, No. 2, Page 107.

[0039] The K-values ​​shown in Table 1 above are merely representative in nature and in no way limit the scope or type of PVC resins or combinations of resins that may be used in the subject PVC compositions and vinyl films or layers.

[0040] If multiple resins are used, they are typically blended with one another to form a uniform blended resin composition. The decision to blend PVC resins may be driven by the desire to optimize the clarity, moisture permeability, dimensional stability, or tensile properties of the vinyl film. In some embodiments, the composition comprises a blend of a low molecular weight PVC resin, a medium molecular weight PVC resin, and a high molecular weight PVC resin.

[0041] In some embodiments, a blend of a low molecular weight PVC resin, a medium molecular weight PVC resin, and a high molecular weight PVC resin is used to provide a relatively high initial reflectivity of a laminate as described herein, compared to a corresponding laminate utilizing a vinyl layer having a single PVC resin. In addition, in many embodiments, a vinyl layer utilizing a blend of a low molecular weight PVC resin, a medium molecular weight PVC resin, and a high molecular weight PVC resin exhibits a desired low modulus and an acceptable low degree of shrinkage.

[0042] A variety of PVC resins can be used for low, medium and high molecular weight PVC resins. Many of these resins are commercially available. Non-limiting examples of high molecular weight PVC resins include Mexichem Vestolit G171, Formosa Formolon F-NVW and SCG Chemicals PG770. Non-limiting examples of medium molecular weight PVC resins include Mexichem Vestolit G178, Formosa Formolon-1071 and SCG Chemicals PG740. Non-limiting examples of low molecular weight PVC resins include Mexichem Vestolit G173, Formosa Formolon-24A and SCG Chemicals PG620. It should be understood that the present subject matter is not limited to any of these PVC resins and may include other PVC resins.

[0043] In certain embodiments, when a mixture of low, medium, and high molecular weight PVC resins is utilized, it may be beneficial to utilize a combination of PVC resins in a specific weight ratio to each other. In some embodiments, the concentration ratio of low molecular weight PVC, medium molecular weight PVC, and high molecular weight PVC is 15-60:15-60:40-90. It should be understood that the present subject matter is not limited to the use of PVC resins in the amounts or weight ratios described, but includes other amounts, ratios, and / or weight ratios of PVC resins.

[0044] In some embodiments, PVC resins exhibit relatively low plasticizer solubility, which prevents the migration of one or more components in the composition, especially protective additives. In some embodiments, high molecular weight PVC is used to prevent the migration of one or more components in the vinyl composition, especially protective additives. PVC resins also have low solubility in plasticizers, thereby promoting the plasticizer to act on the surface of PVC molecules. PVC resins can also be more compatible with solvents used in the composition. In some embodiments, PVC resins exhibit high solvent solubility.

[0045] B. Nanocrystalline Materials

[0046] In some embodiments, the compositions described herein also include one or more nanocrystalline materials. As used herein, "nanocrystalline material" refers to a polycrystalline material having a grain size of typically about 1 nm to about 100 nm. Nanocrystalline materials fill the gap between amorphous materials without any long-range order and conventional coarse grain materials. Although there are different definitions, nanocrystalline materials are generally defined as crystallites (grains) less than 100 nm in size. A grain size of 100–500 nm is generally considered to be "ultrafine" grains.

[0047] Nanocrystalline materials can be prepared using a variety of methods. The methods are generally classified based on the phase of matter that the material transforms through before forming the nanocrystalline final product.

[0048] Solid-state process

[0049] Solid-state processes do not involve melting or evaporating materials and are generally performed at relatively low temperatures. Examples of solid-state processes include mechanical alloying using high-energy ball mills and certain types of severe plastic deformation processes.

[0050] Liquid Process

[0051] Nanocrystalline materials can be produced by rapid solidification from a liquid using processes such as melt spinning. This generally produces an amorphous material that can be converted to a nanocrystalline material by annealing above the crystallization temperature. Liquid processing is often used to prepare nanocrystalline metals.

[0052] Gas phase process

[0053] Films of nanocrystalline materials can be produced using vapor deposition processes such as MOCVD.

[0054] Solution Process

[0055] Some metals, particularly nickel and nickel alloys, can be made into nanocrystalline foils using electrodeposition.

[0056] In some embodiments, the nanocrystalline material comprises or is nanocrystalline cellulose or nanocellulose. Nanocellulose refers to the term for nanostructured cellulose. It may be cellulose nanocrystals (CNC or NCC), cellulose nanofibers (CNF) (also known as microcellulose cellulose (MFC)), or bacterial nanocellulose (which refers to the cellulose of the nanostructure produced by bacteria). NCC may comprise or be natural cellulose (i.e., unsubstituted cellulose). In other embodiments, NCC may be functionalized to change / improve the physical, chemical and / or mechanical properties of the material. Functionalization may include covalent or non-covalent means of functionalizing NCC. For example, NCC may be functionalized to improve or enhance the printing properties and / or thermal stability of PVC. In some embodiments, the functionalized or substituted NCC is not poly (cinnamoyloxyethyl methacrylate) (PCEM).

[0057] CNF is a material composed of nanometer-scale cellulose fibrils with a high aspect ratio (length-to-width ratio). Typical fibril widths are 5-20 nanometers over a wide range of lengths, typically several micrometers. It is pseudoplastic and exhibits thixotropy, a property of certain gels or fluids that are thick (viscous) under normal conditions but become less viscous when shaken or stirred. When shear forces are removed, the gel recovers most of its original state. The fibrils are separated from any source containing cellulose, including wood fibers (pulp fibers), by high pressure, high temperature, and high-speed impact homogenization, grinding, or microfluidization (see manufacturing below).

[0058] Nanocellulose can also be obtained from natural fibers by acid hydrolysis, producing highly crystalline and rigid nanoparticles that are shorter (100s to 1000 nm) than nanofibrils obtained by homogenization, microfluidization or grinding routes. The resulting material is called cellulose nanocrystals (CNCs).

[0059] The ultrastructure of nanocellulose from various sources has been extensively studied. The ultrastructure of nanocellulose from various sources has been commonly studied using methods such as transmission electron microscopy (TEM), scanning electron microscopy (SEM), atomic force microscopy (AFM), wide angle X-ray scattering (WAXS), small incident angle X-ray diffraction, and solid-state 13 C cross-polarization magic angle spinning (CP / MAS), nuclear magnetic resonance (NMR) and spectroscopy techniques were used to characterize the morphology of dried nanocellulose.

[0060] Pulp chemistry has a significant effect on the nanocellulose microstructure. Compared to enzyme pretreated nanocellulose (where the fibril width is 10-30nm), carboxymethylation increases the number of charged groups on the fibril surface, making the fibrils easier to release and producing smaller and more uniform fibril widths (5-15nm). Crystallinity and crystalline structure of nanocellulose. Nanocellulose exhibits cellulose crystal I organizational structure and the crystallinity is not changed by the preparation of nanocellulose. Typical values ​​for crystallinity are about 63%.

[0061] In for example, as NCC is added in the method for organosol, the concentration of NCC can change based on film or the desired property of the laminated product comprising film.In some embodiments, the concentration of NCC in the organosol for cast film is about 0.01% to about 5%, about 0.01% to about 3%, about 0.01% to about 1%, about 0.1% to about 1% or about 0.1% to about 0.5% in the organosol weight.In some embodiments, the concentration of NCC in the organosol is less than about 3.5%, 3.0%, 2.5%, 2.0%, 1.5%, 1.0%, 0.5%, 0.25% or 0.1% in the organosol weight.The NCC added in situ in the PVC resin process can be used than the lower concentration of NCC directly mixed in the vinyl organosol.NCC is added in the vinyl organosol and can reduce viscosity ( Figure 2 ), which may negatively impact the ability to cast vinyl at higher concentrations.

[0062] C. Plasticizer

[0063] In some embodiments, the compositions described herein also include one or more plasticizers. A variety of plasticizers can be used for the vinyl compositions and vinyl films of this theme. In some embodiments, the plasticizer exhibits thermal stability properties. In some embodiments, the plasticizer exhibits low solubility with other additives and / or components of the vinyl composition.

[0064] In some embodiments, the selected plasticizer is bio-based. As used herein, the term "bio-based" refers to a plasticizer comprising a bio-product or a renewable agricultural material (including plants, animals and / or marine materials) or formed therefrom. The example of a bio-based plasticizer is a plasticizer such as one prepared by soybean, corn and / or other agricultural products. Another example of a bio-based plasticizer is a plasticizer made from natural oils and fats. Typically, compared with non-bio-based plasticizers, bio-based plasticizers show better biodegradability due to the presence of epoxides. In a particular embodiment, bio-based plasticizers have inherent thermal stability characteristics, but have lower solubility with other additives and / or components of the composition. Although monomer plasticizers can be used in certain embodiments, due to their low molecular weight, monomer plasticizers are not usually used for long-term weathering applications. Therefore, in the vinyl composition according to this theme, a more complex polymer plasticizer with a higher molecular weight is used.

[0065] Non-limiting examples of commercially available bio-based plasticizers that can be used in vinyl compositions include, but are not limited to, Alpha 200, Alpha 200C, Alpha210 and Alpha 220; obtained from Emery Oleochemicals D 81, D 82S, B 316 Special Grade, 1234, 9789, 1208 and 1233 Special; obtained from Roquette ID; obtained from Oxea DOSX and ABTC; DOSX from Myriant; and 1044, 2644, 01422, PLSGreen 5 and PLS Green 8. It should be understood that the present subject matter is not limited to any one of these plasticizers and that other plasticizers may be used.

[0066] In some embodiments, the plasticizer used in the vinyl composition exhibits a relatively high degree of incompatibility and / or is insoluble with respect to water. In some embodiments, such plasticizers are derived from adipic acid and a polyol. A non-limiting example of such a plasticizer is 656 (CAS No. 208945-12-4), commercially available from BASF.

[0067] D. Acid scavenger

[0068] In some embodiments, the compositions described herein or the films made therefrom comprise one or more acid scavengers. A variety of acid scavengers can be used in the vinyl compositions and vinyl films described herein. It is speculated that the ultimate degradation of the vinyl film is inevitable. Once HCl begins to form, the vinyl degradation rate increases exponentially. Acid scavengers are used to neutralize the initially formed HCl, thereby extending the life of the vinyl film product.

[0069] Epoxides are the most commonly used type of acid scavenger in vinyl films. In some embodiments, the use of one or more epoxides in vinyl compositions can improve various properties and performances of vinyl films and laminates using the vinyl films. In certain applications, epoxides provide dual functionality as plasticizers and acid scavengers. This increases the flexibility of the vinyl film and enhances thermal stability by delaying the onset of thermal degradation.

[0070] However, the addition of epoxides to vinyl compositions can result in reduced reflectivity and / or other undesirable optical properties of the vinyl film and laminate. The epoxide can migrate into the spacer layer and plasticize the spacer layer. Once plasticized, the spacer layer may be more susceptible to deformation at elevated temperatures. Once the spacer layer is deformed, the metal layer may no longer be able to produce a retroreflective product.

[0071] In view of the potential limitations of epoxides as acid scavengers for films used in retroreflective applications, other materials can be used as acid scavengers. In some embodiments, the acid scavenger is a solid particle, such as hydrotalcite. For retroreflective materials, such solid materials may not be ideal because it is desirable to avoid anything between the metal layer and the outer surface of the vinyl layer that may refract or diffuse light. For such applications, compatible liquids with low refractive indices, such as 1-methylimidazole, can be used. The potential for large particles to refract light makes NCC a cellulose choice that is superior to CNF.

[0072] E.UV Stabilizer

[0073] In some embodiments, one or more UV stabilizers may be used in the vinyl compositions and vinyl films described herein. A variety of UV stabilizers may be used. The most common types of UV stabilizers are cyanoacrylates, benzophenones, benzotriazoles, triazines, and oxanilides. Certain UV stabilizers may migrate, which may adversely affect the physical properties of the resulting vinyl films and laminates. Other UV stabilizers have unexpected plasticizing properties, which may be lost if the UV stabilizer is unstable in the vinyl film. Therefore, in some embodiments, one or more specific UV stabilizers will not adversely affect the physical properties of the compositions or films described herein, and in some embodiments, may result in improved performance.

[0074] In some embodiments, the UV stabilizer is oxalanilide or an oxalanilide-based compound. UV stabilizers of this type are commercially available from various sources under the Clariant trade name Hostavin 3206liq and the BASF trade name Tinuvin 312.

[0075] Other UV stabilizers include oligomeric hindered amine light stabilizers (HALS), which are commercially available under the Clariant trade name Hostavin 3070P. Other examples of hindered amine light stabilizers that are commercially available and can be used in vinyl compositions include Clariant's Hostavin TB-03, Hostavin TB-04, and AddWorks LXR 308; BASF's Tinuvin 123 and 292; and 3V's Uvasorb HA10 and HA88FD. HALS can be used as a reinforcing agent for the primary UV stabilizer. The UV stabilizer to HALS ratio can range from 9:1 to 6:4. Any combination of these UV stabilizers and HALS can be used.

[0076] F. Heat stabilizer

[0077] In some embodiments, one or more thermal stabilizers may be used in the vinyl compositions and vinyl films described herein. In some embodiments, the thermal stabilizers include calcium (Ca) and zinc (Zn); in other embodiments, barium (Ba) and zinc (Zn) systems are preferred. In some embodiments, it has been found that an increased Ba / Zn ratio reduces one or more adverse effects that may occur when other thermal stabilizers are used. In those embodiments, the barium-zinc thermal stabilizer has a Ba / Zn molar ratio of greater than 3.85:1, and in some cases greater than 4:1. In certain applications, suitable thermal stabilizers may include phosphorus (P).

[0078] For barium-zinc heat stabilizers, it was found that selecting a heat stabilizer with a higher barium content increased the solvent ink dot diameter. And selecting a heat stabilizer with a lower zinc content tended to reduce the solvent ink dot diameter, and the effect was greater than the higher barium content. Thus, for heat stabilizers containing two metals, and particularly for barium-zinc heat stabilizers, it has been found that the barium to zinc ratios described herein surprisingly produce vinyl films and laminates with excellent properties.

[0079] In some embodiments, heat stabilizers that are relatively incompatible (eg, insoluble) with the plasticizers used in the vinyl composition result in improved properties of the resulting vinyl film and / or laminate.

[0080] Examples of commercially available heat stabilizers that have been found to promote improved properties of vinyl films and laminates include Mark 4887 and Mark 4825 available from Galata Chemicals. Mark 4887 and Mark 4825 are both barium-zinc heat stabilizers. A variety of other potentially useful heat stabilizers are available from other suppliers, including, for example, Valtris Specialty Chemicals, Adeka, Baerlocher, Reagens, Kolon Industries, and Halstab. However, it should be understood that the subject matter is not limited to any one of these heat stabilizers, but rather one or more other heat stabilizers may be used.

[0081] G. Printing Enhancement Additives

[0082] In some embodiments, in addition to NNC, one or more print enhancing additives may be used in the vinyl compositions and vinyl films described herein. Non-limiting examples of print enhancing additives include surfactants, polydimethylsiloxanes, and / or other agents. Combinations of one or more of these agents may be used.

[0083] The vinyl composition may also include one or more surfactants. Surfactants may be used in the vinyl composition to improve the properties of the resulting vinyl film. The one or more surfactants are selected from nonionic surfactants, anionic surfactants, cationic surfactants, or combinations thereof. Non-limiting examples of potentially suitable surfactants include BYK-3560, DISPERBYK, DISPERBYK-2200, and BYK-4512 available from BYK Additives and Instruments; BYK-4512 available from BASF; Ultra PA 4512; and available from Kusumoto Chemicals LF-1985, LPH-810, SPL-85, UVX-35 and UVX-36. For example, polyacrylate-based surfactants can improve dot circularity compared to vinyl compositions without such agents.

[0084] The vinyl composition may include one or more polydimethylsiloxanes, which are generally referred to as PDMS in the art. Although a variety of PDMS agents can be used in the vinyl composition, in many embodiments, it may be preferred that the PDMS exhibits a viscosity greater than 40 cSt. Non-limiting examples of potentially suitable PDMS agents include DMS-S15, DMS-S21, and DMS-S27 available from Gelest; Xiameter OFX-5211 and Xiameter PMX-0156 available from Dow Corning; PSF-50 cSt and PSF-100 cSt available from ClearCo; and PDMS agents available from Sigma Aldrich. In certain applications, it has been found that the use of certain printing enhancement additives results in improved printed dot roundness. The polydimethylsiloxane in the vinyl composition may also improve the uniformity of the printed dots. The combined use of two of these agents can produce printed dots with improved dot shape and size compared to the use of a vinyl composition containing only one of these agents.

[0085] In some embodiments, the heat stabilizers, UV stabilizers, and acid scavengers are selected so that they exhibit improved compatibility, and in certain embodiments, exhibit optimal compatibility with each other and solvents. In some embodiments, the Ba / Zn ratio of the heat stabilizer can be increased to reduce the negative impact on printing. In some embodiments, hindered amine light stabilizers (HALS) are used and added to the UV stabilization package. HALS are generally solids that are not easily soluble in solvents, which will ensure that some UV protection is retained in the vinyl. However, for retroreflective products, liquid HALS are preferred if available. Higher molecular weight acid scavengers can also be used.

[0086] In some embodiments, NCC and PDMS are combined for improved printability. A composition having a NCC / PDMS weight ratio of 1.2:1 produces an optimal dot diameter for digital solvent printing. In some embodiments, the total concentration of NCC and PDMS does not exceed 1.00 wt % in the final vinyl film.

[0087] The resulting vinyl compositions may be more weatherable, with delayed generation of nicotine products. Tailored solubility additives combined with higher molecular weight PVC can reduce migration of key additives to the surface, which would impair printing and bonding properties, including, for example, adhesion to urethane bonding layers used in many laminate products. The resulting products are clear and glossy (as desired), and the resulting products exhibit improved solvent digital printability.

[0088] The vinyl composition may contain one or more light stabilizers, particularly one or more hindered amine light stabilizers or HALS as described above. These are typically in addition to the UV stabilizers described above. In many cases, these agents are in solid form under ambient conditions. In addition, in many embodiments, the HALS exhibits low solvent solubility to prevent migration of components or additives in the vinyl composition.

[0089] H. Solvents and / or diluents

[0090] The vinyl composition may include one or more solvents. A variety of solvents may be used, many of which are commercially available, such as HiSol 10 and Aromatic 100, which are blends of various petroleum distillates. Addition of solvents to the vinyl composition promotes blending and mixing of the components, application of the composition, and / or formation of a vinyl layer or film. The solvent is typically removed from the composition during drying, curing, and / or layer formation.

[0091] III. Multilayer structure

[0092] The NCC-containing films described herein can be used in a variety of applications, including but not limited to graphic applications, such as automotive and building packaging; reflective applications, such as road and traffic signs, trains and other commercial vehicles, etc.; and label applications. Such films are typically incorporated into multilayer structures or laminates that contain other components suitable for a particular application. Exemplary components include but are not limited to spacer layers, tie layers, adhesive layers, layers containing optical components, metal layers, barrier layers, release liners, and combinations thereof.

[0093] The thickness of vinyl film can be varied. However, if the film is too thin, the reduction of the obtained modulus and tensile strength may cause the film to break or tear easily when removing, processing or using. If the tensile strength is too low, then when operating after the film processing such as "weeding" sign cutting letters, the matrix may also break easily. The maximum thickness of the vinyl film realizes a good balance between the conformability and the intensity of the film. The thickness greater than the thickness described herein may show unacceptable conformability characteristics. In some embodiments, the thickness of the vinyl film containing nanocrystalline material (such as, nanocrystalline cellulose) is less than about 3 mils (75 microns), 2.5 mils, 2.0 mils, 1.5 mils, 1.0 mils or 0.5 mils.

[0094] A. Spacer layer

[0095] The laminates described herein for retroreflective applications may include a spacer layer disposed between the optical layer / zone and the metal layer. The spacer layer is used to hold and secure the optical layer and / or the optical components of the layer or zone. The spacer layer is also used to properly space the optical components from the metal layer and / or to properly space the optical components from the outer surface of the laminate. Resins that can be used for the spacer layer include various partially amorphous or semi-crystalline thermoplastic polymers that are transparent or substantially transparent and generally have a soft stage at which the optical components can be embedded in the spacer layer.

[0096] In some embodiments, the adhesion between the spacer layer and the adjacent layer or material is greater than the tensile strength of the material. Acrylic resins, polyvinyl butyral (PVB), aliphatic urethanes and polyesters are particularly useful polymeric materials for spacers because they have stability to outdoor environmental conditions. Copolymers of ethylene and acrylic acid or methacrylic acid, vinyl, fluoropolymers, polyethylene, cellulose acetate butyrate, polycarbonate and polyacrylate are other examples of polymers or polymeric materials that can be used for spacers in the laminated products of the present subject matter. Combinations of these components can also be used.

[0097] In some embodiments, the material used in the spacer layer is polyvinyl butyral (PVB). In some embodiments, the PVB is commercially available PVB, such as Butvar B-90 from Solutia or B-08SY from TRiiSO.

[0098] B. Optical components

[0099] The laminates described herein for retroreflective applications may also include at least one optical component layer or region. The layer or region comprising the optical component is typically embedded in or along a portion of the spacer layer, and typically along a face of the spacer layer. The optical component is typically transparent or substantially transparent and is in the form of microspheres having a certain refractive index.

[0100] The optical components used in the laminate, if in particle form, can have an average diameter ranging from about 25 to about 300 microns, 30 to about 120 microns, or about 40 to about 80 microns. The refractive index of the optical component is typically in the range of about 1.9 to about 2.5, about 2.0 to about 2.3, or about 2.10 to about 2.25.

[0101] Glass microspheres can be used for optical components, but ceramic microspheres, such as those made by sol / gel techniques, can also be used. The refractive index and average diameter of the microspheres, as well as the refractive indices of the other layers and the spacer layer, determine the thickness of the spacer layer. The microspheres can be chemically or physically treated to improve the bonding of the microspheres to the layers and / or regions of the laminate. For example, the microspheres can be treated with fluorocarbons or adhesion promoters such as aminosilanes to improve adhesion, or the spacer layer in which the microspheres are embedded can be flame treated or corona discharged to improve the adhesion of the spacer layer and the microspheres to any adjacent layers.

[0102] In some embodiments, a laminate may include one or more prismatic structures in place of or in combination with the glass microspheres or other particulate optical components described herein. Thus, it should be understood that the present subject matter includes a variety of optical components that can be used in laminates and / or retroreflective products.

[0103] C.Metal layer

[0104] In some embodiments, the laminate may further comprise at least one metal layer. In some embodiments, the metal layer comprises a reflective metal, such as silver or aluminum.

[0105] A variety of methods can be used to apply or place the metal. In some embodiments, the metal is applied to the second surface of the spacer layer by an evaporation method (thermal or electron beam) or by cathode sputtering (magnetron or reaction). The thickness of the reflective layer depends on the specific metal used and is generally about 500 to 1,000 nanometers. However, it should be understood that the present subject matter includes various variations of this layer.

[0106] D. Adhesive

[0107] In some embodiments, laminated product may include one or more layers or the district of adhesive. In some embodiments, the first adhesive layer includes one or more structural adhesives. The example of this material includes but is not limited to urethane adhesives. However, the pressure-sensitive adhesive with suitable bond strength and refractive index is also suitable as the first layer of adhesive. As mentioned above, in many cases, the adhesive used for the second adhesive layer includes a pressure-sensitive adhesive.

[0108] The first adhesive layer used in the laminate is usually arranged between the vinyl film or layer and the spacer. As described, in some embodiments, the first adhesive layer comprises one or more urethane adhesives. In many formulations, the urethane adhesive is prepared by combining a polyol component and an isocyanate component with an optional crosslinking agent. Crosslinking and / or chemical bonding with certain functional groups in the adjacent vinyl layer (such as-OH groups, especially those in the plasticizer in the vinyl layer) can result in improved adhesion and physical attachment between the vinyl layer and the first adhesive layer.

[0109] Almost any pressure-sensitive adhesive (PSA) composition known in the art can be used in the laminated product. Such adhesive compositions are described, for example, in "Adhesion and Bonding," Encyclopedia of Polymer Science and Engineering, Vol. 1, pp. 476-546, Interscience Publishers, Second Edition, 1985. Such compositions typically contain adhesive polymers such as natural or recycled rubber, styrene-butadiene rubber, styrene-butadiene or styrene-isoprene block copolymers, polyisobutylene, poly(vinyl ether) or poly(acrylate) esters as the main component. The pressure-sensitive adhesive composition may contain other materials such as resin tackifiers, including rosin esters, oil-soluble phenolic resins and polyterpenes; antioxidants; plasticizers, such as mineral oil or liquid polyisobutylene. Fillers are not used in the first layer of adhesive for highly reflective articles because this scatters light and reduces the retro-reflectivity of the article. Fillers can be used in applications where the maximum reflectivity is limited. The choice of pressure sensitive adhesive for use in any of the subject laminates is not critical, and those skilled in the art are familiar with many suitable pressure sensitive adhesives for a particular application.

[0110] Either or both of the first adhesive layer and / or the second adhesive layer may be patterned. Either or both of these layers may optionally include one or more non-continuous adhesive regions and / or include regions without adhesive.

[0111] It should be understood that each of the above adhesives can be provided as a solvent-based adhesive, an emulsion, a hot melt adhesive, a UV-curable or radiation-curable adhesive. In addition, each adhesive can be made removable or permanent. The system and performance characteristics of the adhesive can be selected according to the needs of the specific purpose or intended application.

[0112] E. Release liner

[0113] In some embodiments, the vinyl-based laminate includes one or more release liners. The liner typically masks or covers the otherwise exposed surface or area of ​​the second adhesive, which is typically a PSA.

[0114] Release coating liners may include release coating articles containing more than one sheet material including alternating paper layers and polymer layers to provide desired properties. The following examples of laminates illustrate the types of laminates that can be used as release coating liners in the subject laminates: release composition / polyethylene / paper; release composition / paper / polyethylene; release composition / polyvinyl chloride / paper; release composition / polyethylene / paper / polyethylene / tissue paper, etc.; in these examples of release coating liners, the polyethylene base film can be from low density to high density, and the paper material can be any paper material.

[0115] In some embodiments, various layer arrangements may be used, as long as at least a portion of the spacer layer is disposed between the optical component and the metal layer. In other embodiments, the laminate is characterized in that the first adhesive layer is disposed between the vinyl film and at least one of (i) the optical component and (ii) the spacer layer. In another embodiment, the metal layer is disposed between the spacer layer and the second adhesive layer. In another embodiment, the vinyl film is disposed adjacent to the first adhesive layer. In another embodiment, the optical component is disposed between the first adhesive layer and the metal layer. The present subject matter is not limited to any of these specific cases, and includes laminates that exhibit combinations of these features and embodiments.

[0116] F. Printing layer

[0117] In some embodiments, the laminate includes one or more printed layers or zones. Printing or printing compositions may be applied or otherwise deposited on a vinyl film or layer or other layers of the laminate. It is also contemplated that one or more auxiliary layers such as a topcoat and an over-laminate film may be applied to the vinyl layer and then printed on the topcoat or over-laminate film. This subject also includes applying a topcoat, a protective layer or an over-laminate film to the printed surface of the laminate.

[0118] A variety of printing compositions can be used in conjunction with the present subject matter. Many such compositions are known in the art and / or commercially available. Non-limiting examples of such printing compositions include inks, coatings, lacquers, and toners. The printing composition can be applied by known techniques. In many cases of the present subject matter, the printing composition is applied directly to the outer surface of the vinyl layer of the laminate. As described herein, due to the characteristics of the vinyl layer, the resulting printed layer, area, text, and / or design obtains improved performance. In addition, the addition of NCC to a composition containing a vinyl resin (e.g., an organosol, from which a film is cast) shows improved eco-solvent print dot formation.

[0119] The laminate structure can have a desired thickness to provide a laminate with suitable properties and performance desired for a particular purpose or intended use. In one embodiment, the total thickness of the laminate structure is from about 1.5 mils to about 15 mils (about 35 microns to about 350 microns). In another embodiment, the total thickness of the laminate structure is from about 3 mils to about 10 mils (about 70 microns to about 254 microns). In yet another embodiment, the total thickness of the laminate structure is from about 5 mils to about 8 mils (about 120 microns to about 205 microns).

[0120] IV. Manufacturing Method

[0121] Figure 1 is a schematic diagram of one embodiment of a process for forming poly(vinyl chloride). In a batch reactor 1, vinyl chloride monomer 7 is mixed and reacted with a mixture 8 of water, nanocrystalline cellulose, and optional additives to form poly(vinyl chloride) containing nanocrystalline cellulose (wet product with residual monomer) 9. The wet product 9 is discharged in a vent 2 to remove residual monomer vapor. The residual monomer vapor is then moved to a monomer recovery unit 4 and then recycled back to the batch reactor 1. The wet product is then moved to a stripping unit 3, which removes additional residual monomer vapor and sends it to a monomer recovery unit 4, which is also recycled back to the batch reactor 1. The wet product is then moved to a dehydration unit 5, where water is removed and recycled back to the batch reactor 1, and the residual wet product is moved to a drying unit 6 to remove additional water, leaving a final dry poly(vinyl chloride) containing nanocrystalline cellulose.

[0122] 1 Batch Reactor

[0123] 2 Monomer vapor exhaust device

[0124] 3 Stripping unit

[0125] 4 Monomer recovery device

[0126] 5 Dehydration device

[0127] 6 Drying device

[0128] 7 Vinyl chloride monomer

[0129] 8 Water, nanocrystalline cellulose and optional additives

[0130] 9 Poly(vinyl chloride) containing nanocrystalline cellulose (wet)

[0131] 10 Poly(vinyl chloride) containing nanocrystalline cellulose (dry)

[0132] 11 Water removed

[0133] 12 Steam

[0134] 13 Water Reuse

[0135] In certain embodiments, the poly(vinyl chloride) is granular in nature. In certain embodiments, the nanocrystalline cellulose is deposited on the surface of the poly(vinyl chloride) particles.

[0136] In certain embodiments, the method further comprises the step of drying the aqueous dispersion to form a dried composite.

[0137] In certain embodiments, the nanocrystalline cellulose is present in the composite at a level of less than 3.5 wt % based on the total weight of the composite, preferably less than 1 wt % based on the total weight of the composite, and more preferably less than 0.5 wt % based on the total weight of the composite.

[0138] In certain embodiments, the method further comprises the steps of preparing an organosol and casting a film from the organosol, wherein the organosol comprises: a composite; and an organic fluid for suspending or dispersing the composite.

[0139] In certain embodiments, the method further comprises the steps of drying the aqueous dispersion to form a dried composite; melting the dried composite to form a molten composite; and calendering a film from the molten composite.

[0140] The present invention is further defined in the following examples, wherein all parts and percentages are by weight unless otherwise stated. It should be understood that these examples, although showing preferred embodiments of the present invention, are provided only by way of illustration. Through the above discussion and these examples, those skilled in the art can determine the essential characteristics of the present invention, and, without departing from its spirit and scope, can make various changes and modifications to the present invention to adapt it to various uses and conditions. Example

[0141] Example 1: Improved digital solvent printing

[0142] Addition of NCC to vinyl organosols showed improved dot formation for eco-solvent printing ( Figure 3 ). As the NCC level increases, the ink dots become rounder and more uniform. The addition of PDMS at lower CNC dosages shows uniformity.

[0143] Example 2: Improved Thermal Stability

[0144] The thermal stability is determined by using the Metrastat dehydrochlorination test method from Metrohm. This is a device designed to measure the thermal stability of PVC and other chlorine-containing polymers. The device induces a decomposition based on heating the sample, which leads to the release of gaseous HCl. A continuous nitrogen flow through the sample transports this HCl from the sample container to a container with distilled water. The conductivity of the water is measured continuously. As soon as HCl appears, the conductivity in this container increases. The time when an increase of 50 μS / cm is reached compared to the start of the measurement is called the stabilization time.

[0145] The addition of NCC also resulted in a significant increase in thermal stability when added to the vinyl organosol. The NCC concentration was evaluated as a function of critical conductivity time (sec). The results are shown in Figure 4 The critical conductance time of the vinyl organosol without NCC was 8,000 seconds. In contrast, the addition of NCC at concentrations of 0.1%, 0.3%, and 0.5% resulted in critical conductance times of 9,000 seconds, 10,000 seconds, and 10,500 seconds, respectively.

[0146] When ranges are used herein for physical properties (eg, molecular weight) or chemical properties (eg, chemical formula), all combinations and subcombinations of ranges that specify embodiments are intended to be included.

[0147] The disclosures of each patent, patent application, and publication cited or described herein are hereby incorporated by reference in their entirety.

[0148] Those skilled in the art will appreciate that many changes and modifications may be made to the preferred embodiments of the present invention, and such changes and modifications may be made without departing from the spirit of the present invention. Therefore, the appended claims are intended to cover all equivalent changes that fall within the true spirit and scope of the present invention.

Claims

1. A method comprising: A composition is provided to a reactor, wherein the composition comprises: Vinyl chloride monomer; Nanocrystalline cellulose; and water; polymerizing the composition to form a composite, wherein the composite comprises: Poly(vinyl chloride); and Nanocrystalline cellulose; wherein the composite is in the form of an aqueous dispersion, and wherein the nanocrystalline cellulose is present in the composite at a level of less than 0.5 wt % based on the total weight of the composite.

2. The method of claim 1, wherein the poly(vinyl chloride) is poly(vinyl chloride) particles; and wherein the nanocrystalline cellulose is deposited on the surface of the poly(vinyl chloride) particles.

3. The method of claim 1, further comprising: The aqueous dispersion is dried to form a dried composite.

4. The method of claim 1, further comprising: An organosol is prepared, wherein the organosol comprises: the composite; and an organic fluid for suspending or dispersing the composite; as well as The organosol is cast into a film.

5. The method of claim 1, further comprising: drying the aqueous dispersion to form a dried composite; melting the dried composite to form a molten composite; as well as A film is calendered from the molten composite.

6. A product produced by the method of any one of claims 1 to 5.

Citation Information

Patent Citations

  • Nanocellulosic compositions

    US20190048147A1

  • PVC compositions, films, laminates and related methods

    US20190144656A1